Mating: Парење - Kolozova, Katerina; Ruskovska, Rodna (Identities: Journal for Politics, Gender and Culture, 2002)
Author(s): Katerina Kolozova | Катерина Колозова Title (English): Mating Title (Macedonian): Парење Translated by (English to Macedonian): Rodna Ruskovska | Родна Русковска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 2 (Winter 2002) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 161-166 Page Count: 6 Citation (English): Katerina Kolozova, “Mating,” Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 2 (Winter 2002): 161-166. Citation (Macedonian): Катерина Колозова, „Парење“, превод од англиски Родна Русковска, Идентитети: списание за политика, род и култура, т. 1, бр. 2 (зима 2001): 161-166.